Hyperphosphorylation induces self-assembly of τ into tangles of paired helical filaments/straight filaments - Alonso, Alejandra del C. (The National Academy of Sciences, 2001)
The microtubule-associated protein τ is a family of six isoforms that becomes abnormally hyperphosphorylated and accumulates in the form of paired helical filaments (PHF) in the brains of patients with Alzheimer's disease (AD) and patients with several other tauopathies. Here, we show that the abnormally hyperphosphorylated τ from AD brain cytosol (AD P-τ) self-aggregates into PHF-like structures on incubation at pH 6.9 under reducing conditions at 35°C during 90 min. In vitro dephosphorylation, but not deglycosylation, of AD P-τ inhibits its self-association into PHF. Furthermore, hyperphosphorylation induces self-assembly of each of the six τ isoforms into tangles of PHF and straight filaments, and the microtubule binding domains/repeats region in the absence of the rest of the molecule can also self-assemble into PHF. Thus, it appears that τ self-assembles by association of the microtubule binding domains/repeats and that the abnormal hyperphosphorylation promotes the self-assembly of τ into tangles of PHF and straight filaments by neutralizing the inhibitory basic charges of the flanking regions.